Cales: A Corpus-Based Archive Of Learner English In Sarawak / Prof. Madya Dr. Simon Botley@Faizal Hakim ... [et al.] - Hakim, Botley @ Faizal; De Alwis, Caesar; Metom, Lilly; Mohd. Esa, Ismaizza (Universiti Teknologi MARA Cawangan Sarawak, 2005)
This report describes a new learner corpus project called CALES (Corpus-based Archive of Learner English in Sarawak). The project has collected 89,000 words of learner writing in the form of argumentative essays written by students taking English proficiency courses in UiTM’s Sarawak Branch Campus.The project follows the methodological principles laid down by the International Corpus of Learner English (ICLE) project in Belgium (Granger et. al., 2002), and the data has been analysed in order to classify different types of error found in the corpus. A number of observations have been made concerning the most frequent errors in the data, as well as some correlations between the errors and the social, educational and linguistic attributes of the learners who produced the essays.